HDAC4: an emerging target in diabetes mellitus and diabetic complications - Yiqi Lin; Yuetong Li; Caiying Ke; Ying Jin; Wanwen Lao; Yiling Wu; Yang Liu; Xinyi Kong; Jie Qiao; Aixia Zhai; Changlong Bi (European Journal of Medical Research)
Abstract Diabetes mellitus (DM) is a metabolic disease with complex pathogenic mechanisms. Histone deacetylase 4 (HDAC4) is a member of an important family of epigenetic modifications. An increasing amount of research indicates that HDAC4 may control DM by modulating the epigenetic and post-translational expression of numerous transcription factors and taking part in different signaling cascades. In this review, HDAC4 was reported to control the differentiation, growth, and function of pancreatic β-cells. Furthermore, HDAC4 regulates glucose metabolism by targeting GLUT4 and FOXO1 and further modulates insulin signaling pathways through cytoplasmic-nuclear shuttling. Moreover, HDAC4 has also been implicated in the regulation of diabetic nephropathy, diabetic cardiomyopathy, diabetes osteoporosis, diabetic wounds, and diabetic encephalopathy. Therefore, HDAC4 is consider to be a viable therapeutic target for the treatment of DM and its complications. HDAC inhibitors and other targeted inhibitions of HDAC4 provide us with new ideas for developing novel intervention strategies. This article reviews the role of HDAC4 in diabetes mellitus and its complications.